Pelaksanaan Lelang Aset Desa Berdasarkan Peraturan Bupati Kudus Nomor 38 Tahun 2017 tentang Pedoman Pengelolaan Aset Desa (Kajian di Desa Megawon, Jati, Kudus) - Mochamad Ekky Sofwan Putra (Jurnal Hukum Lex Generalis, 2025)
This study aims to determine the implementation of village asset auctions in Megawon Jati Village, Kudus, based on Kudus Regent Regulation Number 38 of 2017 and identify obstacles and solutions. Using an empirical juridical method with a descriptive approach, primary and secondary data were analyzed qualitatively. The results indicate that the auction was conducted through preparation, implementation, and post-auction management stages. The main obstacles were administration and low community participation. Solutions were implemented through increasing committee capacity, improving documentation, and more intensive outreach.